2013
DOI: 10.1007/s10499-013-9646-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound evaluation of the gonadal structure in sex-reversed rainbow trout females

Abstract: Ultrasound approach has been used to assess morphology of the gonadal structure in the sex-reversed rainbow trout females (neomales) provided in the course of 11b-hydroxyandrostenedione treatment applied within gonadal differentiation period. Eighteen matured individuals (in range 38.0-48.6 cm of body length and 802-1644 g of body weight) were scanned using digital ultrasound apparatus (DP-6900 model) Mindray Ltd., during the spawning season. After screening, fishes were killed to validate the morphological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Although the absolute size of testis and semen volume of neo‐males was higher, the lower gonadosomatic index (GSI) and semen volume per kilo of fish indicate that, normal males were better primed reproductively. The GSI values observed in our study (6.45 ± 1.1%, and 4.19 ± 0.8% for normal and neo‐males respectively) are similar to those obtained by Hliwa, Bah, Kuzminski, Dobosz, and Ciereszko () in neo‐males of rainbow trout (3.9%), and by Fjelldal, Hansen, and Huang () in mature normal males of Atlantic salmon (7.3%). Similarly, Geffen and Evans () reported that normal males of rainbow trout were generally smaller but had higher GSI than neo‐males.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the absolute size of testis and semen volume of neo‐males was higher, the lower gonadosomatic index (GSI) and semen volume per kilo of fish indicate that, normal males were better primed reproductively. The GSI values observed in our study (6.45 ± 1.1%, and 4.19 ± 0.8% for normal and neo‐males respectively) are similar to those obtained by Hliwa, Bah, Kuzminski, Dobosz, and Ciereszko () in neo‐males of rainbow trout (3.9%), and by Fjelldal, Hansen, and Huang () in mature normal males of Atlantic salmon (7.3%). Similarly, Geffen and Evans () reported that normal males of rainbow trout were generally smaller but had higher GSI than neo‐males.…”
Section: Discussionsupporting
confidence: 90%
“…Presence of two symmetrical and elongated gonad lobes, each having a well‐developed spermatic duct running to the caudal direction and emptying into the genital papilla is typical in normal males of S. salar (Geffen & Evans, ; Hliwa et al, ). In contrast, the observed asymmetry and irregular sac‐like testicular lobes with poorly developed ducts are likely precluding sperm expression by neo‐males (Robles et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Fish gonadal development is quite plastic and in many species, the response to environmental perturbations that encompass the period of sex differentiation is masculinization (Baroiller & D'Cotta, ; Ospina‐Alvarez & Piferrer, ; Piferrer, ). The masculinization of genotypic females generates phenotypic males (Hliwa, Bah, Kuźmiński, Dobosz, & Ciereszko, ) that are termed neomales (Pandian & Sheela, ). These neomales are capable of producing viable sperm (Piferrer, ).…”
Section: Discussionmentioning
confidence: 99%
“…This results in an increase in the proportion of males (18) and implies that some genetic females (XX or ZW females) in CSD species, or fish that otherwise would develop as females in a PSD system, end up developing as phenotypic males despite their genetic makeup. These masculinized or sex-reversed females are called "neomales," and have testicular structure (19) and gene expression profiles similar or identical to those of males (20,21) and can produce viable sperm. In fact, in several farmed species with male heterogametic sex determination, hormone-or heatinduced XX neomales are crossed with regular XX females and used for the production of all-female stocks (22).…”
mentioning
confidence: 99%